Aortic morphology post type A acute aortic syndrome: Prognosis significance and association with 24‐hour blood pressure‐monitoring parameters. Issue 5 (16th March 2020) - Delsart, Pascal; Soquet, Jérôme; Ramdane, Nassima; Ramond, Charline; Mugnier, Agnes; Rousse, Natacha; Ledieu, Guillaume; Bical, Antoine; Loobuyck, Valentin; Jegou, Bruno; Modine, Thomas; Hysi, Ilir; et al.
Abstract: Background: After an emergent surgery for type A acute aortic syndrome, medical management is based on optimal blood pressure (BP) control. We assessed the prognostic significance of BP monitoring and its relationship with aortic morphology following type A acute aortic syndrome. Methods: The data of 120 patients who underwent BP monitoring after a type A acute aortic syndrome from January 2005 to June 2016 were retrospectively collected. The first CT angiogram performed after surgery was used for the morphological analysis. Results: The population included 79 males, with an overall mean age of 60 ± 12 years. Seven patients (5.8%) died during a median follow‐up of 5.5 years. The median delay between BP monitoring and discharge was 3 (1‐5) months. The mean 24‐hour BP of the cohort was 127/73 mm Hg ± 10/17. During follow‐up, different parameters of BP monitoring were not associated with the risk of aortic events. However, the diameter of the false lumen of the descending thoracic aorta was the best predictor associated with the risk of new aortic events during follow‐up, particularly for the threshold of 28 mm or more ( P < .001; Hazard ratio 4.7[2.7‐8.2]). The diameter of the false lumen was associated with night‐time systolic BP ( P = .025; r = .2), 24‐hour pulse pressure ( P = .002; r = .28), and night‐time pulse pressure ( P = .008; r = .24). Conclusion: The risk of new aortic events following type A acute aortic syndrome is associated with the size of the residual false lumen, but not directly with BP parameters. Night‐time BP parameters are associated with the size of the residual false lumen.